(untitled) (Communications in Computational Chemistry, 2025)
A simple model based on the two-electron two-orbital textbook problem is presented and used to analyze pairwise interatomic interactions in metal-ligand bonding. In particular the two types of covalency discussed during the last decade for actinide-ligand interactions, overlap/interaction driven and energy-near-degeneracy driven covalency, as well as their influence on the bond strengths and interatomic charge build-up are discussed. The hydration complexes M(H_2O)^4+_n of selected tetravalent lanthanide and actinide ions are used to probe the performance of the model for an analysis of calculations as well as for predictions.